2017
DOI: 10.1016/j.biomaterials.2017.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Co-coating of receptor-targeted drug nanocarriers with anti-phagocytic moieties enhances specific tissue uptake versus non-specific phagocytic clearance

Abstract: Nanocarriers (NCs) help improve the performance of therapeutics, but their removal by phagocytes in the liver, spleen, tissues, etc. diminishes this potential. Although NC functionalization with polyethylene glycol (PEG) lowers interaction with phagocytes, it also reduces interactions with tissue cells. Coating NCs with CD47, a protein expressed by body cells to avoid phagocytic removal, offers an alternative. Previous studies showed that coating CD47 on non-targeted NCs reduces phagocytosis, but whether this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Rodriguez et al ( 115 ) demonstrated that CD47-derived peptides coupled to polystyrene beads reduced their uptake by macrophages, and prolonged their circulation in mice. In line, different types of NC (polystyrene, PLGA) conjugated with an ICAM-1 targeting antibody for endocytic uptake by activated endothelial cells showed clearly reduced unspecific liver accumulation when conjugated in addition with CD47 ( 116 ). In a different approach, NC were coated with cell membranes derived from red blood cells to exploit their endogenous high level surface expression of CD47 and other “don’t eat me signals” [reviewed in Ref.…”
Section: Other Corona Proteins That Affect Nc Adsorption To Cellsmentioning
confidence: 73%
“…Rodriguez et al ( 115 ) demonstrated that CD47-derived peptides coupled to polystyrene beads reduced their uptake by macrophages, and prolonged their circulation in mice. In line, different types of NC (polystyrene, PLGA) conjugated with an ICAM-1 targeting antibody for endocytic uptake by activated endothelial cells showed clearly reduced unspecific liver accumulation when conjugated in addition with CD47 ( 116 ). In a different approach, NC were coated with cell membranes derived from red blood cells to exploit their endogenous high level surface expression of CD47 and other “don’t eat me signals” [reviewed in Ref.…”
Section: Other Corona Proteins That Affect Nc Adsorption To Cellsmentioning
confidence: 73%
“…Therefore, apart from PEG, additional functionalization or coatings are necessary, e.g. binding of CD47 to the surface of the nanoparticles [76,117,118]. Another focus is the enhancement of magnetic properties by equipping nanoparticle cores with higher iron content [43] and design larger implants out of a highly permeable, remanent ferromagnetic material [26], probably with additional surface coatings [52].…”
Section: Discussionmentioning
confidence: 99%
“…The use poly(ethylene glycol) (PEG) to minimize these non-specific interactions, which unfortunately has a similar effect on specific ones, has been extensively discussed [192]. Finally, surface coating of the “don’t eat me” signal provided by cluster of differentiation (CD) 47 on drug carriers has been shown to lower phagocytic internalization [193] without affecting specific binding and uptake by co-coated targeting moieties [194].…”
Section: Alterations In the Vesicular Transport Of Cellsmentioning
confidence: 99%